Women in the Technology Labour Market - Ana M. González Ramos (Revista Española de Investigaciones Sociológicas (REIS), 2017)
The technology labour market, where women are in the minority, represents an opportunity for employment in Spain. This paper analyses the data from the Labour Force Survey (known by its abbreviation in Spanish, ?EPA?) in relation to the population employed in the technological sector. The gender segregation of the employed population is analysed by economic sector, together with the employment characteristics of women employed in the technological sector. The results indicate that job expectations are good for women in this sector, but also that they have a higher risk of being overqualified, which suggests that there are persistent discrimination factors. Finally, women expressed greater concern than their male counterparts about the excessive working hours, which raises the need for structural change in organisations.